Interplay between Charge Injection, Electron Transport, and Quantum Efficiency in Ambipolar Trilayer Organic Light‐Emitting Transistors. Issue 5 (15th January 2022) - Moschetto, Salvatore; Benvenuti, Emilia; Usta, Hakan; Ozdemir, Resul; Facchetti, Antonio; Muccini, Michele; Prosa, Mario; Toffanin, Stefano
Abstract: The fascinating characteristic of organic light‐emitting transistors (OLETs) of being electrical switches with an intrinsic light‐emitting capability makes them attractive candidates for a wide variety of applications, ranging from sensors to displays. To date, the OLET ambipolar trilayer heterostructure is the most developed architecture for maximizing device performance. However, a major challenge of trilayer OLETs remains the inverse correlation between external quantum efficiency and brightness under ambipolar conditions. The complex interconnection between electroluminescent and ambipolar charge transport properties, in conjunction with the limited availability of electron transport semiconducting materials, has indeed hampered the disruptive evolution of the OLET technology. Here, an in‐depth study of the interplay of the key fundamental features that determine the device performance is reported by exploring electron transport semiconductors with different properties in ambipolar trilayer OLETs. Through the selection of compounds with tailored chemical structures, the relation between intrinsic optoelectronic characteristics of the electron transport semiconductor, energy level alignment within the structure, and morphological features is unraveled. Furthermore, the introduction of a suitable electron injector at the emissive/semiconducting layers interface sheds light into the bidimensional nature of OLETs that is a distinguishing factor of this class of devices with respect to prototypical organic light‐emitting diodes. Abstract : The complex functioning of the trilayer heterostructure of organic light‐emitting transistors is hindering their technological development. Here, valuable insight on the bidimensional nature of ambipolar trilayer organic light‐emitting transistors is gained by elucidating the interplay between optoelectronic characteristics of the electron transport semiconductor, energy level alignment within the structure, and morphological features.